2022
DOI: 10.4209/aaqr.220184
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on PM2.5 Purification Characteristics of Different Filter Units in Enclosed Environments

Abstract: Many epidemiological studies have shown that long-term exposure to high PM2.5 concentrations can significantly increase the morbidity and mortality of different diseases. Air cleaners are effective in removing PM2.5. In the present research, different filter units were tested to determine their PM2.5 filtration efficiency. The filter face velocity was adjusted to 50%, 75%, 100%, 125%, and 150% of the corresponding rated airflow. The single-pass efficiencies, resistances, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The air purifier's performance should be evaluated under different environmental conditions to determine its effectiveness in various outdoor settings. Zhang et al (2022) indicated that the use of cleaners with different filter units will elevate the level of PM filtration. They pointed out that with increase in wind speed, the effectiveness of filters decreases.…”
Section: Limitationsmentioning
confidence: 99%
“…The air purifier's performance should be evaluated under different environmental conditions to determine its effectiveness in various outdoor settings. Zhang et al (2022) indicated that the use of cleaners with different filter units will elevate the level of PM filtration. They pointed out that with increase in wind speed, the effectiveness of filters decreases.…”
Section: Limitationsmentioning
confidence: 99%